Internet censorship detected in Thailand (Thailand) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Thailand. Data sourced from CensoredPlanet.
Censorship Incident ID: TH-2026-0162. Severity: critical. Confidence: 65%